«In isto libro grosso». Materials and forms of the most ancient accounting register of the Bishop’s Revenue of Milan (1376-1386) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2020)
The paper analyzes extrinsic and instrinsic characters of the Liber grossus, the oldest accounting manuscript of the Milan Archdiocese (1376-1386), to find out times, responsibles and aims at the very origin of its production and conservation.
Keywords: Accounting manuscript; Milan Archdiocese; Antonio da Saluzzo